2003
DOI: 10.1111/j.0014-3820.2003.tb01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenies in Mice Selected for High Voluntary Wheel-Running Activity. I. Mean Ontogenies

Abstract: Abstract. The evolutionary importance of postnatal ontogenies has long been recognized, but most studies of ontogenetic trajectories have focused exclusively on morphological traits. For animals, this represents a major omission because behavioral traits and their ontogenies often have relatively direct relationships to fitness. Here four replicate lines of house mice artificially selected for high early-age wheel running and their four replicate control lines were used to evaluate the effects of early-age dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 77 publications
7
35
0
Order By: Relevance
“…Based on these results, we hypothesize that these age-related patterns are common features of the relationship between age and locomotor performance in a wide range of organisms. The shape of the patterns seems to match descriptions of other age-related locomotor performances in different species, such as flight performances in Drosophila (31), honeybees (32), and codling moths (33), maximal sprint speed in dogs and horses (34)(35)(36), physical activity in different rodents and monkeys (16,27,28), grip strength in mouse lemurs (15), hunting rates and success in wolves (37), swimming speed in zebrafish (38), and voluntary activity and electrotactic behavior in C. elegans (29,39). Likewise, other performance traits might follow a similar pattern, such as biting force in mouse lemur (40), cognitive performances in Rhesus monkey (41), attentiveness in domestic dogs (42), pharynx pumping rate in C. elegans (43), and perhaps even photosynthetic yield in cotton leaves (44).…”
Section: A Robust Nonlinear Pattern Describes Age-related Physiologicmentioning
confidence: 53%
See 2 more Smart Citations
“…Based on these results, we hypothesize that these age-related patterns are common features of the relationship between age and locomotor performance in a wide range of organisms. The shape of the patterns seems to match descriptions of other age-related locomotor performances in different species, such as flight performances in Drosophila (31), honeybees (32), and codling moths (33), maximal sprint speed in dogs and horses (34)(35)(36), physical activity in different rodents and monkeys (16,27,28), grip strength in mouse lemurs (15), hunting rates and success in wolves (37), swimming speed in zebrafish (38), and voluntary activity and electrotactic behavior in C. elegans (29,39). Likewise, other performance traits might follow a similar pattern, such as biting force in mouse lemur (40), cognitive performances in Rhesus monkey (41), attentiveness in domestic dogs (42), pharynx pumping rate in C. elegans (43), and perhaps even photosynthetic yield in cotton leaves (44).…”
Section: A Robust Nonlinear Pattern Describes Age-related Physiologicmentioning
confidence: 53%
“…We used respectively 33 (27,28) who conducted studies of life-long voluntary activity in two groups of mice: A control population composed of 79 mice and a population of 80 mice from the 16th generation of selection for high wheel-running activity. All the details of the population selection and living conditions are available in Morgan et al (27).…”
Section: Comparison Between Chicago Marathon 2006 and 2007mentioning
confidence: 99%
See 1 more Smart Citation
“…As expected for mice of this age, some increase in physical activity level occurs as they are still undergoing physical maturation (Swallow et al 1999;Morgan et al 2003). This age-related trend makes it diYcult to interpret the daily variability in raw wheel revolutions with respect to normal maturation versus inherent control (regulation) of physical activity level.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies of these lines of mice from earlier generations have demonstrated that daily wheel-running distances increase for approximately 5 weeks following Wrst exposure to wheels at weaning (3 weeks of age) or shortly thereafter (Swallow et al 1999;Morgan et al 2003). In the present study, we analyzed data from a later generation and considered weeks 3-5 of wheel access (6-8 weeks of age), in order to parallel our previous studies of human adolescents and young adults Eisenmann 2006, 2007a, b;Wickel et al 2007).…”
Section: Discussionmentioning
confidence: 99%